Myelinated Fibers and Saltatory Conduction in the Shrimp The Fastest Impulse Conduction in the Animal Kingdom - Xu, Ke.; Terakawa, Susumu; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
In 1961, neurobiologists found that the conduction velocity of the nerve impulse in the giant nerve fiber of the Penaeus shrimp abdominal nerve cord was over 200 m/s, the highest speed of information transmission ever observed in the animal kingdom. The peculiar myelin sheath with its unique nodal structure and the electrical properties of the nerve fibers of the shrimp have continued to be investigated for a quarter of century and are now fully described in this book. The investigation dispels the commonly held belief that the fastest recorded impulse conduction is about 120 m/s in the thickest vertebrate myelinated nerve fibers. In the shrimp, researchers found a completely novel type of functional node in the giant fiber which they designated as the fenestration node. In portions of the myelinated fiber, the fenestration node furnished the sites of excitation. Also discovered was a new strategy for increasing impulse conduction in the shrimp. The book includes a section on the formation of the fenestration node and the discovery of a strategy that allows the shrimp to escape its predators by an action of the fastest velocity. The data presented in this volume on the myelin sheath of invertebrates present a new direction for this field and a rich source of information for neurobiologists worldwide.
Keywords: Life sciences; Neurosciences; Biochemistry; Cytology; Cell membranes; Neurobiology; Life Sciences; Neurobiology; Neurosciences; Animal Biochemistry; Cell Physiology; Membrane Biology